The Influence of Third-Party Funds, Non-Performing Finance, and Return on Assets on Murabahah Financing in Islamic Commercial Banks During the Period 2018-2022 - Layla Nurkhasanah; Setiyawan Gunardi; Edo Segara Gustanto; M. Arif Kurniawan (Mutanaqishah: Journal of Islamic Banking, 2023)
This study aims to determine the effect of Third Party Funds, Non-Performing Finance, and Return On Assets on Murabahah Financing at Sharia Commercial Banks for the period 201 8-2022. Using quantitative research methods with the object of research at Sharia Commercial Banks. Sampling using purposive sampling with a total of 50 samples. The data analysis technique used is multiple linear regression analysis with hypothesis tests by t-test (partial) and F-test (simultaneous). Testing in this study used SPSS 26. The results showed that DPK had a significant positive effect on Murabahah Financing with tcount 6.235 > t-table of 1.67866, NPF had no effect and was not significant on Murabahah Financing with tcount 0.494 > t-table of 1.67866, and ROA has a positive and significant effect on Murabahah Financing with tcount 2.047 < t-table of 1.67866. Simultaneously, DPK, NPF, and ROA affect Murabahah Financing with Fcount 19.008 > Ftable of 2.81. Then based on the results of the Adjusted R Square of 0.524 shows that the ability of the independent variable in explaining the dependent variable is 52.4%, and the remaining 47.6% is explained by other variables that are not included in this study.